Estimation of Equivalent Pore Aspect Ratio in Rock Physics Models and Validation Using Digital Rocks - Luiz Eduardo Queiroz; Dario Grana; Celso Peres Fernandes; Tapan Mukerji; Leandro Passos de Figueiredo; Iara Frangiotti Mantovani (Geosciences)
Complex pore structures with multiple inclusions challenge the predictive accuracy of rock physics models. This study introduces a novel method for estimating a single equivalent pore aspect ratio that optimizes rock physics model predictions by minimizing discrepancies with experimental measurements in porous rocks with multiple inclusions with variable aspect ratios and proportions. The proposed methodology uses digital rock physics numerical simulations for validation. A comparative analysis is conducted between the equivalent aspect ratio derived from optimized rock physics models, numerical simulations, and the aspect ratio distribution estimated from digital rock samples. The approach is tested on both synthetic and real core samples, demonstrating its robustness and applicability to field data, including core samples and well log data. The validation results confirm that the method enhances predictive accuracy and offers a versatile framework for addressing pore complexity in subsurface rock formations.